The Place And Role Of The Tourism Industry In The Economy Of The Middle East Countries (Eurasian Journal of History, Geography and Economics, 2025)
This article is devoted to the analysis of the current state and development trends of the tourism industry in the Muslim countries of the Middle East. The place, role and priority importance of this industry in national economies are revealed. In the article, economic indicators reflecting the state of international tourism are given in table form. Data on the development of tourism in the Muslim countries of the Middle East are compared with the indicators of the leading countries of the industry in the world. Also, the importance of tourism development in Uzbekistan and its forecasts for the near future are outlined